PROFIT, POWER, AND PAYOUTS: FAKTOR PENENTU NILAI PERUSAHAAN PERBANKAN DI INDONESIA (2019–2023) - Natonis, Sari Angriany; Purba, Arjuna; Riwu, Yonas Ferdinand (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2025)
This study aims to analyze the influence of profitability, social structure, liquidity, and dividend policy on firm value in banking sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. A quantitative approach was employed using multiple linear regression analysis. The independent variables include Return on Assets (ROA) as a measure of profitability, social structure represented by managerial and majority share ownership, Loan to Deposit Ratio (LDR) as an indicator of liquidity, and Dividend Payout Ratio (DPR) for dividend policy. Firm value, as the dependent variable, was measured using the Tobin’s Q ratio. The sample consisted of seven banking companies selected through purposive sampling over a five-year observation period. The results show that partially, ROA, managerial share ownership, and LDR have a significant effect on firm value, while majority share ownership and DPR do not have a significant effect. Simultaneously, the four independent variables significantly influence firm value. These findings provide valuable insights for bank management, investors, and academics in formulating strategic policies to enhance firm value amid economic uncertainty.